2020
DOI: 10.1111/dom.14121
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide extended release in patients with type 1 diabetes with and without residual insulin production

Abstract: Aims: To test whether a long-acting GLP-1 receptor agonist would improve glucose control in patients with type 1 diabetes (T1D) and to determine whether the presence of residual beta cell function would affect the response. In addition, we sought to determine whether the drug would affect beta cell function. Methods: We performed a randomized placebo-controlled trial of exenatide extended release (ER) in participants with T1D with and without detectable levels of C-peptide. Seventy-nine participants were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In clinical trials with albiglutide [65] and rapamycin and vildagliptin [66], restoration of the betacell function was not observed. However, using vildagliptin, liraglutide or exenatide, the exogenous insulin requirement of patients was reduced [66][67][68].…”
Section: Andandmentioning
confidence: 99%
“…In clinical trials with albiglutide [65] and rapamycin and vildagliptin [66], restoration of the betacell function was not observed. However, using vildagliptin, liraglutide or exenatide, the exogenous insulin requirement of patients was reduced [66][67][68].…”
Section: Andandmentioning
confidence: 99%
“…4950 Liraglutide 1.8 mg in people with type 1 diabetes and higher body mass index decreased HbA 1c , weight, and insulin requirements with no increased hypoglycemia risk 94. However, on the basis of results from a study of weekly exenatide that showed similar results, these effects may not be sustained 51. A meta-analysis of 24 studies including 3377 participants showed that the average HbA 1c decrease from GLP-1 receptor agonists compared with placebo was highest for liraglutide 1.8 mg daily (−0.28%, 95% confidence interval −0.38% to−0.19%) and exenatide (−0.17%, −0.28% to 0.02%).…”
Section: Advances In Treatmentsmentioning
confidence: 99%
“…Glucagon-like peptide-1 receptor (GLP-1R) agonists as adjunctive therapies have been tested in T1D patients (6), and some individuals who are overweight or have detectable levels of C-peptide might benefit from those medications (6). GLP-1R agonists also exert protective effects on bone tissue in vitro and in vivo (7)(8)(9). Some clinical studies have found neutral effects of liragutide on bone, but there was also a few meta-analysis of 16-59 randomized controlled trials with 11,206-49,602 patients with T2DM which showed that compared with placebo and other antidiabetic drugs, liraglutide was associated with a significant reduction in the risk of bone fractures (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%